(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Coagulopathies during pregnancy, including both inherited and acquired disorders, present significant challenges to maternal health. Effective diagnosis and timely intervention are crucial to managing these conditions and preventing complications such as bleeding or thrombosis. Among the various diagnostic techniques, thromboelastography (TEG) offers a comprehensive assessment of coagulation and fibrinolysis, providing valuable insights into the coagulation cascade. This article reviews the role of TEG in the diagnosis of coagulopathies in pregnant women, its clinical applications, advantages over traditional coagulation tests, and its potential in guiding therapeutic strategies. By highlighting recent studies, the article aims to inform obstetricians, hematologists, and laboratory specialists about the integration of TEG in managing coagulopathy-related pregnancy complications.